The Wonders and Curiosities of the Number 9 (Global Journal of Science Frontier Research, 2023)
Numbers are a world full of secrets and wonders that help explain many phenomena and enter the world of games to act as an engine for the human mind and a catalyst for the study of these numbers. For the numbers associated with the number 9, and help us build the number system so that it is divisible by the number 9, in addition to what is related to the result and its properties.